Armies of the Gulf War - Rottman, Gordon L. (Elite series, 1993)
Osprey's examination of US troops during the Persian Gulf War (1990-1991). Besides continuing a long history of world-wide peacekeeping, the commitment of US troops to the Gulf reunified the country and restored a national pride lost in the aftermath of Vietnam. It also proved that the US armed forces were again the most capable military force in the world. This volume by veteran Osprey author Gordon L. Rottman focuses on the structure, equipment, effectiveness, and employment of the 680,000 coalition troops which fought in the Gulf War, covering not only the US forces, but also those of Britain, France, the Arab League and Iraq.